Free cash flow y el valor de la empresa - Pacheco Mexzon, Raimundo Renaun (2011)
The globalization of the economy and the internationalization of capital markets today is quite widespread in the world, that is why there is no place for insulation of different markets, including the stock market and in the case of the Peruvian market is no exception to this reality. In this new context exist a phenomenon of acquisition and merger. The importance that they have taken these acquisitions and mergers of companies makes us think of a technique of recovery that makes it possible to calculate the value of the company to be able to perform this operation without problems and at a fair price. Hence, our concern is to raise a simple model to calculate the value of the company based on the "Free Cash Flow".